GENETIC PARAMETERS FOR Hymenaea courbaril L. CONSERVATION IN SOUTHWESTERN AMAZON - Susana Maria Melo Silva; Karina Martins; Antônio Gilson Gomes Mesquita; Lucia Helena de Oliveira Wadt (Ciência Florestal, 2014)
http://dx.doi.org/10.5902/1980509813326 The loss of diversity in tropical regions has been focus on several governmental and non-governmentaldiscussions, focusing mainly on the fragmentation and destruction of natural ecosystems. However,decisions about the conservation of genetic resources must be guided by population genetic parameters,especially for species with economic interests that are subject to greater human interference. This studyaimed to define and evaluate genetic parameters for the conservation of populations of Hymenaea courbarilin southwestern Amazon. This species is one of the most valuable and intensively exploited wood species inthe Brazilian Amazon. We studied three forest areas prepared for logging in the background of sustainablemanagement. It was calculated with eight microsatellite loci, genetic diversity, intra-population conservationestimators and genetic divergence among populations. Genetic diversity and fixation index were higher inthe low density populations (< 0.08 ind.ha-1). The most density population (0.25 ind.ha-1) showed the lowestgenetic diversity and no inbreeding. The Minimum Viable Area for species conservation was consistent with the reality of the studied areas, with a proviso for one of the populations where there is a need for amuch larger area than the other to conserve populations. The genetic divergence was high (G’ST = 0.344) andthe populations were considered Independent Management Units.